The Validity and Reliability of Live Football Match Statistics From Champdas Master Match Analysis System - Gong, Bingnan; Cui, Yixiong; Gai, Yang; Yi, Qing; Gómez, Miguel-Ángel (Frontiers in Psychology, 2019)
The aim of the present study was to investigate the validity of match variables and the reliability of Champdas Master System used by trained operators in live association football match. Twenty professional football coaches voluntarily participated in the validation of match variables used in the System. Four well-trained operators divided into two groups that independently analyzed a match of Spanish La Liga. The Aiken’s V averaged at 0.84±0.03 and 0.85±0.03 for the validation of indicators. The high Kappa values (Operator 1: 0.92, 0.90; Operator 2: 0.91, 0.88), high intra-class correlation coefficients (varied from 0.93 to 1.00) and low typical errors (varied from 0.01 to 0.34) between the first and second data collection represented a high level of intra-operator reliability. The Kappa values for the inter-operator reliability of were 0.97 and 0.89. The intra-class correlation coefficients and typical errors ranged from 0.90 to 1.00 and ranged from 0.01 to 0.24 for two independent operators within two data collections. The results suggest that the Champdas Master system can be used validly and reliably to gather live football match statistics by well-trained operators. Therefore, the data obtained by the company can be used by coaches, managers, researchers and performance analysts as valid match statistics from players and teams during their professional tasks and investigations.